2010
DOI: 10.7205/milmed-d-09-00149
|View full text |Cite
|
Sign up to set email alerts
|

Hearing and Sound Source Identification With Protective Headwear

Abstract: This study investigated the effect on hearing, sound attenuation, and sound source identification of a prototype neck and two prototype mandible guards attached to a combat helmet. Ten male subjects participated. Free-field hearing thresholds were measured from 250 Hz to 8,000 Hz with the head bare and fitted with the helmet alone and with the guards. Sound source identification was assessed using a horizontal array of eight loudspeakers surrounding the subject. The stimulus was a 75-dB SPL, 300-ms noise burst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Obviously, the skier's ability to localize the direction of the sound may be a very useful tool for that purpose. Nevertheless, to the best of our knowledge, there is no single study in skiing science literature dealing with that problem, even though it has previously been identified in military medicine [14][15][16]. When the sophisticated kevlar protective army helmet is worn, it might diminish the auditory localization ability [16].…”
Section: Resultsmentioning
confidence: 90%
“…Obviously, the skier's ability to localize the direction of the sound may be a very useful tool for that purpose. Nevertheless, to the best of our knowledge, there is no single study in skiing science literature dealing with that problem, even though it has previously been identified in military medicine [14][15][16]. When the sophisticated kevlar protective army helmet is worn, it might diminish the auditory localization ability [16].…”
Section: Resultsmentioning
confidence: 90%
“…In total, 21 adults with normal hearing (10 males and 11 females) with a mean age of 24.3 ± 4.1 years were included in this study. The sample size was estimated according to a previous study (90 % statistical power) on hearing and sound source localisation with military helmets [ 1 ] . Prior to the actual measurements, all subjects underwent otoscopic and audiometric examination of their hearing at the Department of Hearing, Speech and Voice Disorders of the Innsbruck Medical University.…”
Section: Study Participantsmentioning
confidence: 99%
“…This is consistent with other studies on sound source localiza- tion which yielded 94 % correct scores under the condition head bare [ 1 , 2 ] . In a study by Abel et al [ 1 ] , wearing a military combat helmet with neck and mandible guards resulted in a signifi cant decrease in sound source identifi cation of 12 %. In addition, other studies on sound localization [ 2 , 22 ] found that accuracy decreased as the degree of ear coverage increased.…”
mentioning
confidence: 98%
See 2 more Smart Citations